Ambulatory versus home blood pressure monitoring: frequency and determinants of blood pressure difference and diagnostic disagreement - Ntineri A; Niiranen TJ; McManus RJ; Lindroos A; Jula A; Schwartz C; Kollias A; Andreadis EA; Stergiou GS (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objectives: Out-of-office blood pressure evaluation assessed using ambulatory (ABP) or home (HBP) monitoring is currently recommended for hypertension management. We evaluated the frequency and determinants of diagnostic disagreement between ABP and HBP measurements. Methods: Cross-sectional data from 1971 participants (mean age 53.8 +/- 11.4 years, 52.6% men, 32% treated) from Greece, Finland and the United Kingdom were analyzed. The diagnostic disagreement between HBP and daytime ABP was regarded as certain when (i) the two methods diagnosed a different blood pressure phenotype, (ii) the absolute HBP-ABP difference was more than 10/5 mmHg (systolic/diastolic) and (iii) ABP and HBP had a more than 5 mmHg difference from the respective hypertension threshold. Results: In 1574 participants (79.9%), there was agreement between HBP and ABP in diagnosing hypertensive phenotypes (kappa 0.70). Of the remaining 397 participants (20.1%) with diagnostic disagreement, 95 had clinically irrelevant HBP-ABP differences, which reduced the disagreement to 15.3%. When cases with ABP and/or HBP differing <= 5 mmHg from the respective hypertension threshold were excluded, the certain disagreement between the two methods was reduced to 8.2%. Significant determinants of the HBP-ABP difference were age, sex, study center, BMI, cardiovascular disease history, office hypertension and antihypertensive treatment. Antihypertensive drug treatment, alcohol consumption and office normotension independently increased the odds of diagnostic disagreement. Conclusion: These data suggest that there is considerable diagnostic agreement between HBP and ABP, and that these methods are interchangeable for clinical decisions in most patients. However, considerable disagreement between the two methods occurs in an appreciable minority, most likely due to methodological and patient-related factors.